2021
DOI: 10.3390/nu13051703
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Update: Forms, Sources, Kinetics, Detection, Function, Deficiency, Therapeutic Use and Toxicity

Abstract: Vitamin A is a group of vital micronutrients widely present in the human diet. Animal-based products are a rich source of the retinyl ester form of the vitamin, while vegetables and fruits contain carotenoids, most of which are provitamin A. Vitamin A plays a key role in the correct functioning of multiple physiological functions. The human organism can metabolize natural forms of vitamin A and provitamin A into biologically active forms (retinol, retinal, retinoic acid), which interact with multiple molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
154
1
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(169 citation statements)
references
References 350 publications
(478 reference statements)
0
154
1
14
Order By: Relevance
“…There is also evidence supporting the protective role of vitamins against viral infections through multiple mechanisms [44]. EVOO is one of the staple foods of the MetDiet, and is the main dietary source of vitamin E. This vitamin is one of the most effective nutrients enhancing immune function and inflammation [44,50]. Several studies have indicated that vitamin E deficiency impairs both humoral and cell-mediated immune functions [51,52].…”
Section: Mediterranean Diet and Covid-19: Plausible Mechanisms Of Potential Benefitsmentioning
confidence: 99%
“…There is also evidence supporting the protective role of vitamins against viral infections through multiple mechanisms [44]. EVOO is one of the staple foods of the MetDiet, and is the main dietary source of vitamin E. This vitamin is one of the most effective nutrients enhancing immune function and inflammation [44,50]. Several studies have indicated that vitamin E deficiency impairs both humoral and cell-mediated immune functions [51,52].…”
Section: Mediterranean Diet and Covid-19: Plausible Mechanisms Of Potential Benefitsmentioning
confidence: 99%
“…Studies have shown that the accumulation of carotenoids and flavonoids contributes to the seeds’ palatability and nutritional value [ 36 , 37 ]. As an important provitamin A, carotenoids can be metabolized to retinol, effectively preventing vision loss [ 38 ]. By comparing the transcript levels of carotenoid structural genes between green and yellow color millets, the role of carotenoids in the formation of yellow millet color has been proven [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids are transformed into retinyl esters or β-carotene through a series of reactions and are secreted into the bloodstream associated with micelles. The absorption and metabolism of vitamin A and carotenoids in the intestine and the role of the proteins involved are described in detail in these recent updates from Carazo et al [ 28 ].…”
Section: Structure Sources and Absorption Of Vitamin A And Carotenoidsmentioning
confidence: 99%